Strategic thinking and its impact on creative performance: An exploratory study of the opinions of a sample of officers and employees of the Department of Unified National Card Affairs in the holy Karbala - Alwan Al-Taie, Faisal; Maytham Abdul Hussein Al-Ali, Bahaa (Iraqi Journal for Administrative Sciences, 2024)
The aim of the research is to know the extent to which the dimensions of the independent variable can affect the strategic thinking represented by (strategic intent, time thinking, directed hypotheses, opportunity thinking and organizational thinking) and the dependent variable creative performance in its dimensions represented (flexibility, fluency, originality and a sense of problems) in the decisions of officers and employees of the Affairs Department The unified national card in the holy Karbala, which was searched. The research relied on the exploratory descriptive approach in collecting, analyzing, and interpreting its data. The questionnaire was adopted as a main tool in collecting data from a sample of (70) employees from the researched section, in addition to conducting personal interviews for a number of officers of the rank of major and above and the directors of departments and divisions. A set of methods were used. The statistic that helped in analyzing the research evidence and testing its hypotheses represented by statistical tools (including iterations, Boxplot method, Kurtosis and Skewness) to validate the natural distribution of data, confirmatory factor analysis, Alpha Kornbach coefficient, arithmetic averages and standard deviations Pearson Correlation, R2, and T Tests, based on Turnkey Statistical Programs (SPSS.V. 23). The research reached a set of conclusions, the most important of which is the high awareness of the current research variables by the research sample organization, upgrading the organization and accessing prominent competitive centers and creating guidance systems that are employed through training programs that develop and establish in the minds of leaders and human resources the nature of the interactive relationship between the variable of strategic thinking and its use to build creative performance For individuals, the research concluded with a set of recommendations that contribute to clarifying the relationship between research variables and its dimensions and setting means and mechanisms that can be applied to the reality of the researched organization and spreading a culture of strategic thinking in all the joints and sections of the subject System.